Kepuasan dan minat ibu hamil menggunakan saran pelayanan persalinan - Nur Djanah; Suherni Suherni (Jurnal Kesehatan Ibu dan Anak, 2016)
Assessment of the health service by comparing services that they expect with the service they receive, they tend to repeat toreturn when satisfied and will leave or move if not satisfied. One indicator to measure the interest of pregnant women in usingmeans of service delivery is by measuring the satisfaction of pregnant women against the perception of health care servicesreceived. Objective: to know the relationship between the level of satisfaction with the use of the means of Labor Ministryinterest in pregnant women that the ANC method: analytical design description Design cross-sectional. Subjects research 67pregnant women using consecutive sampling corresponding to the criteria of inclusion and exclusion. The collection of datausing questionnaires that have already tested the validity and reliability. Data analysis using Chi-Square. Results: of the 67respondents 89.5% said interest and 10.5% saying not interested in using the means of service delivery, as well as 85% saysatisfied and 15% say not satisfied in accepting the ANC services. Based on testing the correlation of Chi-Squared obtainedthe value of X-squared 4.8028 and p-value 0.02841 with sig < 0.05. This research showed that there was a significantpositive relationship between satisfaction with the interest of pregnant women that the ANC is in using the means of servicedelivery. Conclusion: The more satisfied expectant mothers who did the ANC than the higher interest in using the means ofservice delivery.